2001
DOI: 10.1046/j.1365-2222.2001.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids decrease vascularity of the bronchial mucosa in patients with asthma

Abstract: These findings suggest that inhaled corticosteroid treatment of asthma reduced airway wall vascularity during airway remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 28 publications
1
71
0
Order By: Relevance
“…This may be explained by the fact that they included patients with asthma who were being treated with inhaled corticosteroids in their analysis. In previous studies, ORSIDA et al [16] and the present authors [21] have shown that anti-inflammatory Values are presented as mean (range). M: male; F: female; FEV1: forced expiratory volume in one second; pred: predicted; Dmin: airway hyperresponsiveness as the minimum cumulative unit is equal to 1 min of 1.0 mg?mL -1 aerosol inhalation of methacholine.…”
Section: Discussionmentioning
confidence: 52%
“…This may be explained by the fact that they included patients with asthma who were being treated with inhaled corticosteroids in their analysis. In previous studies, ORSIDA et al [16] and the present authors [21] have shown that anti-inflammatory Values are presented as mean (range). M: male; F: female; FEV1: forced expiratory volume in one second; pred: predicted; Dmin: airway hyperresponsiveness as the minimum cumulative unit is equal to 1 min of 1.0 mg?mL -1 aerosol inhalation of methacholine.…”
Section: Discussionmentioning
confidence: 52%
“…Angiogenesis in asthma may play multiple roles in disease progression, including the recruitment of inflammatory cells to the airways, the contribution to altered airway physiology, and the secretion of a variety of mediators that determine or regulate the inflammatory response (27,28,77). Interestingly, increased vascularization of the asthmatic lung appears to be the only component of airway remodeling that is fully reversible with treatment using glucocorticosteroids (78). Taken together, these data suggest that neovascularization in asthma contributes to the disease process and may serve as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by SONT et al [49] showed that subjects treated with corticosteroids over a period of 2 yrs experienced a lower rate of mild exacerbations, an improved FEV1 and a reduction in the thickness of the subepithelial layer compared with the control group. In a double-blind study of 28 asthmatic subjects, HOSHINO et al [50] demonstrated that treatment with the inhaled steroid beclomethasone dipropionate significantly reduced the vessel number and vascularity in the airways of steroid treated patients. Further study showed that biopsy samples taken before and after treatment with an inhaled steroid revealed a decrease in inflammatory cells and a reduced amount of epithelial damage after 10 yrs, although bronchial hyperresponsiveness remained the same [51].…”
Section: Reversibility Of Remodelling?mentioning
confidence: 99%